(untitled) (Italian Journal of Public Health, 2012)
Background: the Directly Observed Treatment Short Course (DOTS) strategy was introduced into the tuberculosis control programme of Ebonyi, Southeastern, Nigeria in 1996. The impact of the programme on the treatment outcomes for smear-positive tuberculosis has not been assessed ever since. We assessed the trends in treatment outcome for new smear-positive pulmonary tuberculosis between 1999 and 2008. Methods: we conducted a retrospective analysis of the Ebonyi state Ministry of Health quarterly smear-positive tuberculosis statistical returns. Patients were treated and treatment outcome categories computed according to the WHO/National Tuberculosis Control Programme’s guidelines. Chi-square for trends was used to determine significance. Results: the number of smear-positive cases who registered for treatment fell from 1 361 patients in 1999 to 977 in 2008 (Trend χ2=349; P<0.001). The follow-up smear results at month two were not available for 16% of the patients in 1999; this unavailability decreased to 1.7% in 2008. The negative conversion rate at month two increased from 77.5% in 1999 to 95.9% in 2008 (Trend χ2=16.5; P<0.001). Treatment success rose from 74.9% in 1999 to 88.7% in 2008 (Trend χ2=12.8; P<0.001), whilst default rate declined from 12% to 4.3% (Trend χ2=55.6; P<0.001). Though decreasing (Trend χ2=4.64; P=0.031), the annual death rate remained at around 5% during the study period. Conclusions: monitoring, supervision and home visits have improved, and our DOTS programme has achieved an 85% treatment success and declining default rates. However, with the current low case notification and high mortality rates, alternative mechanisms are needed to achieve global stop-TB targets in the State.